Existence of homoclinic solutions for nonlinear second-order coupled systems - Minhós, Feliz (2019)
This work presents sufficient conditions for the existence of homoclinic solutions for second order coupled discontinuous systems of differential equations on the real line without the usual growth condition in the literature. The arguments apply the fixed point theory, Green's functions technique, L¹-Carathéodory functions, lower and upper solutions and Schauder's fixed point theorem.